2019
DOI: 10.1371/journal.pone.0216891
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of consumer-level and research-grade activity trackers in ambulatory settings in older adults

Abstract: Wrist-worn activity trackers have experienced a tremendous growth lately and studies on the accuracy of mainstream trackers used by older adults are needed. This study explores the performance of six trackers (Fitbit Charge2, Garmin VivoSmart HR+, Philips Health Watch, Withings Pulse Ox, ActiGraph GT9X-BT, Omron HJ-72OITC) for estimating: steps, travelled distance, and heart-rate measurements for a cohort of older adults. Eighteen older adults completed a structured protocol involving walking tasks, simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 47 publications
1
100
1
1
Order By: Relevance
“…Studies have evaluated the accuracy of these devices across a variety of functional activities and environmental settings, at different placements on the body, and across a wide range of abilities. There was wide variability in the accuracy of these devices in individuals with normal gait speed [ 42 , 43 ]. Furthermore, in individuals who utilize assistive devices (e.g., cane, walker) [ 44 , 45 , 46 ], walk with slower speeds (e.g., < 0.8 m/s) [ 36 , 37 , 38 , 39 , 40 , 41 ], or have interruptions in continuous walking [ 47 , 48 ], even higher levels of inaccuracy have been identified.…”
Section: The Current Situation With Wearable Device Systemsmentioning
confidence: 99%
“…Studies have evaluated the accuracy of these devices across a variety of functional activities and environmental settings, at different placements on the body, and across a wide range of abilities. There was wide variability in the accuracy of these devices in individuals with normal gait speed [ 42 , 43 ]. Furthermore, in individuals who utilize assistive devices (e.g., cane, walker) [ 44 , 45 , 46 ], walk with slower speeds (e.g., < 0.8 m/s) [ 36 , 37 , 38 , 39 , 40 , 41 ], or have interruptions in continuous walking [ 47 , 48 ], even higher levels of inaccuracy have been identified.…”
Section: The Current Situation With Wearable Device Systemsmentioning
confidence: 99%
“…Previously, wearable chest strap devices with an accompanying wristwatch which uses telemetry, such as the Polar T31 chest strap (Polar, Kempele, Finland), were shown to be a reliable measure of HR compared to gold-standard electrocardiography (ECG) [3]. There are a multitude of studies which have investigated the validity of a wide range of wrist-worn AMs including Apple Watch 1, Fitbit Charge HR, Garmin Forerunner 225, Garmin Vivosmart HR+ and TomTom Cardio [4][5][6][7][8]; however, this is not reflected in the literature with regard to the devices' reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Since the amount of physical activity and sleep is associated with cognitive function and WM integrity in the elderly (Wassenaar et al, 2019), all participants wore a Fitbit Alta HR (Fitbit Inc., San Francisco, CA, USA) for a week to measure both physical activity and total sleep time (TST). Recent studies using the Fitbit have demonstrated that the Fitbit accurately measures physical activity and TST (Stahl and Insana, 2014;Feehan et al, 2018;Tedesco et al, 2019). We used the physical activity energy expenditure (PAEE) measure, which includes low-intensity physical activity (e.g., housework and daily chores) as well as moderate and vigorous physical activity (e.g., jogging and walking; Donahoo et al, 2004;Middleton et al, 2011), and TST that decrease with aging (Campbell and Murphy, 2007).…”
Section: Physical Activity and Total Sleep Timementioning
confidence: 99%